Provoking Punches: Factors Influencing Perceived Violent Reactions to Negative Situations - Eargle, Lisa A.; Burke, Jessica L.; Doucet, Jessica M. (International Journal of Criminology and Sociology, 2023)
Purpose: Violence among college students is an important area of research as this group is at an increased risk of both engaging in and being a victim of violence. As such, the current research aimed to examine factors that may influence violent tendencies among a sample of college students. Method: Data from 101 completed surveys were analyzed. Principal components factor analysis and Cronbach’s alpha resulted in the creation of six independent variables (gun experience, weapons support, anger contagion, witness violence, violent community, and aggressive beliefs) and four dependent variables (competition for resources, social attacks, physical attacks, and unfair situations). OLS regression was used to estimate the impact of each variable on perceptions of reacting with violence to four negative situations. Results: Gun experience and violent community significantly predicted responding violently to both social and physical attacks, while gun support was only predictive of violence in competition for resources. Additionally, aggressive beliefs predicted perceptions of violent responses to physical attacks and in unfair situations. Finally, anger contagion was associated with students reporting an increased likelihood of responding violently to social attacks. Conclusions: While research shows the importance of understanding violence exposure and aggressive norms in creating and improving violence prevention programs and anti-violence strategies, the role that perceptions play is largely absent. Furthermore, this research supports the importance of implementing these programs and strategies among college students/young adults to potentially reduce violence and aggression within this age group.